Research overview and hotspots in the field of recurrent miscarriage: A literature-mining study - Shen, Chaoyan; Zhang, Juan; Zhang, Miaomiao; Yuan, Quan; Lu, Yan; Miao, Lele; Wang, Wei (Frontiers in Medicine, 2025)
Utilizing bibliometric analysis, this study analyzed relevant literature in the field of recurrent miscarriage and systematically reviewed the research overview and hotspots in this field from 2015 to 2024. A total of 3,114 articles were retrieved from the Web of Science Core Collection (WoSCC) database. The analysis demonstrated that the number of papers published in this field was on the rise. Notably, China, Shanghai Jiao Tong University, the American Journal of Reproductive Immunology, and researcher Jing Yang were identified as the most prolific contributors. The most cited researchers and journals were Siobhan Quenby and Fertility and Sterility respectively. The keyword cluster analysis revealed four primary research directions: the pathophysiological processes and associated molecular mechanisms of recurrent miscarriage, the influence of antiphospholipid syndrome and coagulation dysfunction, the role of chromosomal abnormalities and assisted reproductive technologies, and investigations into immunological mechanisms. Co-citation analysis identified key research hotspots in recurrent miscarriage, encompassing risk assessment, pathogenesis, advanced diagnostic methods, biomarker discovery, and single-cell sequencing applications. This study provides a multi-dimensional perspective and comprehensive summary of the research progress in the field of recurrent miscarriage, highlights the importance of multidisciplinary cooperation in this area, and serves as a valuable reference for researchers.